NETWORK SERVICES THAT ALLOW DEVELOPMENT OF PROFESSIONAL COMPETENCE IN STUDENTS BASED ON CLOUD TECHNOLOGIES - Nosirov Jahongir Normurod o‘g‘li (American Journals Publishing, 2024)
In this work, network services that allow the development of professional competence of students are considered.
Keywords: Information, cloud technology, cloud service, education, network services.